Foreign Policy Challenges for the New Administration: Iran and the Middle East - Fares Center for Eastern Mediterranean Studies (Tufts Archival Research Center, 2005)
Occasional Paper No. 5. A report on the conference Foreign Policy Challenges for the New Administration: Iran and the Middle East, March 5-6, 2009, Tufts University, Medford/Somerville, MA.